Mobile phone users as pseudo-brokers in clientelism: evidence from Africa - Chang, Han Il (2022)
Despite a vast literature on clientelism, the impact of Information and Communications Technology (ICT) on clientelistic exchanges remains understudied. In order to fill that gap, we examine whether politicians disproportionately direct private transfers to mobile phone users, who can easily share persuasive messages with their communication partners and thus provide cascading benefits. Analyzing data from the fifth wave of the Afrobarometer survey, we find that mobile phone users are indeed more likely to be targeted and that their chances of being targeted decrease as their feeling of being monitored rises. In addition, the attractiveness of mobile phone users is salient only in urban areas, and mobile phone users are more likely to persuade others to vote for a certain politician upon receiving private transfers. We conclude by discussing the implications of these findings regarding the existence of pseudo-brokers and the impact of ICT on the quality of democracy.